Method for improving optical quality of CVD (Chemical Vapor Deposition) zinc selenide

Through the pretreatment, cleaning, encapsulation and thermal isostatic pressure treatment of CVD zinc selenide blocks, the problems of quality defects such as fog layers and fog spots in zinc selenide materials are solved, the optical transmittance and material quality are improved, and the needs of high-end applications are met.

CN119591056APending Publication Date: 2025-03-11安徽光智科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411625821.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The zinc selenide material grown by CVD method has mass defects such as fog layers and fog spots, resulting in a low yield of high-quality zinc selenide and insufficient light transmittance in the mid-infrared band, which cannot meet the needs of high-end applications.

Method used

Through the pretreatment and screening of zinc selenide blocks, ultrasonic cleaning, cover encapsulation and thermal isostatic pressure treatment, the absorption peaks caused by fog layers, fog spots and Zn-H bonds are eliminated, and the optical transmittance is improved.

Benefits of technology

It effectively eliminates the fog layer and fog spots inside the zinc selenide block, improves the optical transmittance, improves the quality of zinc selenide, and meets the needs of high-end applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591056A_ABST
    Figure CN119591056A_ABST
Patent Text Reader

Abstract

The method for improving the optical quality of CVD zinc selenide comprises the following steps: pre-treating and screening zinc selenide blocks: carrying out material breaking, grinding, rough polishing and detection on zinc selenide grown by a CVD method, screening out the zinc selenide blocks with different quality grades, and further screening out low-quality zinc selenide blocks containing fog layers and fog spots; cleaning: carrying out ultrasonic cleaning on the low-quality zinc selenide block containing the fog layer and the fog spots; a sheath is manufactured in advance according to the size of the zinc selenide block, the sheath is made of a pure metal material resisting the temperature and pressure of heat isostatic pressing, the purity is not lower than 3 N, and the sheath is subjected to ultrasonic cleaning; the zinc selenide block is loaded into a sheath with the proper size, the sheath is vacuumized through a vacuum pump, air in the sheath is removed, and then the sheath is sealed through hot melting welding; performing hot isostatic pressing treatment; and taking out the zinc selenide block with the sheath after the hot isostatic pressing treatment from the standard hot isostatic pressing furnace, removing the sheath sleeved on the zinc selenide block, and carrying out rough polishing detection on the zinc selenide block.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of optical materials, and more particularly to a method for improving the optical quality of CVD zinc selenide. Background Art

[0002] Zinc selenide is a yellow, transparent polycrystalline material with a cubic sphalerite crystal structure that exhibits a high degree of symmetry and stability. Its refractive index is between 2.4 and 2.6, and it has a high transmittance, covering a range of 0.5-15μm. Especially in the mid-infrared band (3-12μm), the transmittance can reach more than 70%. Zinc selenide materials are widely used in lasers, medicine, astronomy, infrared night vision, and other fields due to their excellent optical and thermal properties. It can effectively reduce light loss within the system, improve laser efficiency, and is suitable for manufacturing mid-infrared band laser windows and lenses.

[0003] Zinc selenide is mainly prepared by chemical vapor deposition (CVD). The quality of zinc selenide grown in a chemical vapor deposition chamber has regional distribution. In the chamber, the product quality in a fixed area is generally stable. Common quality defects of CVD zinc selenide include bright spots, red spots, fog layer, fog spots, etc. The proportion of high-quality zinc selenide that can be used in CO2 laser systems is generally small. Zinc selenide materials with serious fog layer (the fog layer is the overall foggy state of the material when illuminated by light in a dark room) and fog spots (the fog spots appear as small cloud-like patches when illuminated by light in a dark room) can only be used for low-end applications, such as coating materials. Therefore, how to improve the yield of high-quality CVD zinc selenide has become an urgent problem to be solved. Summary of the invention

[0004] In view of the problems existing in the background technology, an object of the present disclosure is to provide a method for improving the optical quality of CVD zinc selenide, which can eliminate the fog layer and fog spots inside a low-quality zinc selenide block containing fog layer and fog spots.

[0005] Another object of the present disclosure is to provide a method for improving the optical quality of CVD zinc selenide, which can eliminate the absorption peak near the wavelength of 6.2 μm caused by the Zn—H bond.

[0006] Another object of the present disclosure is to provide a method for improving the optical quality of CVD zinc selenide, which can improve the optical transmittance.

[0007] Thus, a method for improving the optical quality of CVD zinc selenide includes the following steps: S1, zinc selenide block pretreatment and screening: zinc selenide grown by CVD method is cut, ground, roughly polished, and tested to screen out zinc selenide blocks of different quality grades, and then low-quality zinc selenide blocks containing fog layer and fog spots are screened out; S2, cleaning: ultrasonic cleaning of low-quality zinc selenide blocks containing fog layer and fog spots; S3, sheath preparation: pre-preparing a sheath according to the size of the zinc selenide block, the sheath is made of pure metal material resistant to the temperature and pressure of hot isostatic pressing, the purity is not less than 3N, and the sheath is ultrasonically cleaned; S4, sheath packaging: the zinc selenide block is placed in a sheath of suitable size, the sheath is evacuated by a vacuum pump to remove the air in the sheath, and then the sheath is sealed by hot melt welding; S5, hot isostatic pressing treatment, packaging Sub-steps: S51, placing the zinc selenide block encapsulated by the encapsulation in step S4 in a standard hot isostatic pressing furnace, evacuating the furnace after closing it, washing the furnace more than 5 times, and exhausting the air in the furnace; S52, using argon gas with a purity of not less than 5N as the pressure medium, pre-charging the pressure to 30-40MPa, heating it to 750-1000℃ at a heating rate of 0.5-10℃ / min, and performing constant temperature treatment at this temperature, maintaining the pressure in the furnace at 100-200MPa, and the constant temperature treatment time is 1-100h; S53, cooling, cooling to room temperature at a cooling rate of 0.1-5℃ / min; S54, reducing the pressure to normal pressure; S6, taking out the zinc selenide block with the encapsulation after hot isostatic pressing from the standard hot isostatic pressing furnace, removing the encapsulation on the zinc selenide block, and rough polishing the zinc selenide block for inspection.

[0008] The beneficial effects of the present disclosure are as follows. Since zinc selenide begins to sublimate at around 750°C, in the method for improving the optical quality of CVD zinc selenide according to the present disclosure, the zinc selenide block is encapsulated by the sleeve of step S3 through step S4, which can prevent the sublimated gaseous zinc selenide from contaminating the hot isostatic pressing furnace, and the sleeve is in close contact with the zinc selenide block after vacuuming in step S4. Through the hot isostatic pressing treatment of step S5, the sleeve can effectively promote the recrystallization of zinc selenide; it can eliminate the non-stoichiometric ratio of Zn and Se and the holes and inclusions at the grain boundaries, eliminate the absorption peak near the wavelength of 6.2μm caused by the Zn-H bond, reduce the defects and scattering centers inside the CVD zinc selenide, and improve the optical transmittance. Macroscopically, the fog layer and fog spots inside the low-quality zinc selenide block containing fog layer and fog spots screened out in step S1 disappear, and high-quality zinc selenide is obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 Schematic diagram of a simplified structure of an isostatic pressing process according to a method for improving the optical quality of CVD zinc selenide disclosed herein.

[0010] Figure 2 yes Figure 1Exploded view of the housing and ZnSe block.

[0011] Figure 3 These are photos of the low-quality zinc selenide block containing fog layers and fog spots screened out in step S1 of Example 1 and photos of the zinc selenide block detected after step S6.

[0012] Figure 4 It is a comparison of the transmittance between the low-quality zinc selenide block containing fog layer and fog spots screened out in step S1 of Example 1 and the zinc selenide block detected after step S6.

[0013] Figure 5 It is a comparison between the low-quality zinc selenide block containing fog layer and fog spots screened out in step S1 of Example 1 and the grains of the zinc selenide block detected after step S6.

[0014] Figure 6 These are photos of the low-quality zinc selenide block containing fog layers and spots screened out in step S1 of Example 2 and photos of the zinc selenide block detected after step S6.

[0015] Figure 7 It is a comparison of the transmittance between the low-quality zinc selenide block containing fog layer and fog spots screened out in step S1 of Example 2 and the zinc selenide block detected after step S6.

[0016] Figure 8 It is a comparison between the low-quality zinc selenide block containing fog layer and fog spots screened out in step S1 of Example 2 and the grains of the zinc selenide block detected after step S6.

[0017] Fig. 9 These are photos of the low-quality zinc selenide block containing fog layers and spots screened out in step S1 of Example 3 and photos of the zinc selenide block detected after step S6.

[0018] Fig.10 It is a comparison of the transmittance between the low-quality zinc selenide block containing fog layer and fog spots screened out in step S1 of Example 3 and the zinc selenide block detected after step S6.

[0019] Fig.11 It is a comparison between the low-quality zinc selenide block containing fog layer and fog spots screened out in step S1 of Example 3 and the grains of the zinc selenide block detected after step S6. DETAILED DESCRIPTION

[0020] It will be understood that the disclosed embodiments are merely examples of the present disclosure, which may be implemented in various forms, and therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as a basis for the claims and as a representative basis for teaching one of ordinary skill in the art to implement the present disclosure in various ways.

[0021] [Methods to improve the optical quality of CVD zinc selenide]

[0022] Reference Figure 1 and Figure 2 , the method for improving the optical quality of CVD zinc selenide according to the present disclosure comprises the steps of:

[0023] S1, pretreatment and screening of zinc selenide blocks: the zinc selenide grown by CVD method is cut, ground, roughly polished, and tested to screen out zinc selenide blocks of different quality grades, and further screen out low-quality zinc selenide blocks containing fog layers and fog spots;

[0024] S2, cleaning: ultrasonically cleaning the low-quality zinc selenide block containing fog layer and fog spots;

[0025] S3, package preparation: the package is made in advance according to the size of the zinc selenide block. The package is made of pure metal material that can withstand the temperature and pressure of hot isostatic pressing, with a purity of not less than 3N. The package is ultrasonically cleaned;

[0026] S4, package packaging: put the zinc selenide block into a package of suitable size, evacuate the package with a vacuum pump to remove the air in the package, and then seal the package with hot melt welding;

[0027] S5, hot isostatic pressing (HIP) treatment, includes sub-steps:

[0028] S51, placing the zinc selenide block packaged in step S4 in a standard hot isostatic pressing furnace, evacuating the furnace after closing it, and washing the furnace for more than 5 times to exhaust the air in the furnace;

[0029] S52, using argon gas with a purity of not less than 5N as the pressure medium, pre-charging the gas pressure to 30-40MPa, heating the temperature to 750-1000°C at a heating rate of 0.5-10°C / min, and performing constant temperature treatment at this temperature, maintaining the gas pressure in the furnace at 100-200MPa, and the constant temperature treatment time is 1-100h;

[0030] S53, cooling down to room temperature at a cooling rate of 0.1-5°C / min;

[0031] S54, reduce the air pressure to normal pressure;

[0032] S6, taking out the zinc selenide block with the jacket after hot isostatic pressing treatment from the standard hot isostatic pressing furnace, removing the jacket on the zinc selenide block, and performing rough polishing inspection on the zinc selenide block.

[0033] Since zinc selenide begins to sublimate at around 750°C, in the method for improving the optical quality of CVD zinc selenide according to the present disclosure, the zinc selenide block is encapsulated by the sheath in step S3 through step S4, which can prevent the sublimated gaseous zinc selenide from contaminating the hot isostatic pressing furnace, and the sheath is in close contact with the zinc selenide block after being evacuated in step S4. Through the hot isostatic pressing treatment in step S5, the sheath can effectively promote the recrystallization of zinc selenide; it can eliminate the non-stoichiometric ratio of Zn and Se and the holes and inclusions at the grain boundaries, eliminate the absorption peak near the wavelength of 6.2μm caused by the Zn-H bond, reduce the defects and scattering centers inside the CVD zinc selenide, and improve the optical transmittance. Macroscopically, it is manifested as the fog layer and fog spots inside the low-quality zinc selenide block containing fog layer and fog spots screened out in step S1 disappear, and high-quality zinc selenide is obtained.

[0034] In one example, in step S1, grinding is to use a grinder to grind the surface of the zinc selenide block to a surface roughness of no more than Ra0.08μm, and the abrasive is W16 brand corundum purchased from Dongguan Fuchang Surface Treatment Materials Co., Ltd.; rough polishing is to use a polishing machine to polish the surface of the zinc selenide block to a surface roughness of no more than Ra0.03μm, and the rough polishing abrasive is W6 brand corundum purchased from Dongguan Fuchang Surface Treatment Materials Co., Ltd.

[0035] In one example, in step S1, the low-quality zinc selenide block containing fog layer and fog spots is a rectangular piece or a round piece. For example, in one example, the round piece is D50mm×(5-20)mm (i.e., diameter×thickness). The rectangular piece is 50mm×100mm×(5-20)mm (i.e., width×length×thickness).

[0036] The cleaning of the zinc selenide block in step S2 is used to remove dirt on the surface of the zinc selenide block. In one example, in step S2, ultrasonic cleaning is to use an eight-slot ultrasonic cleaning machine to put the zinc selenide block into the slots in the order of 1-8 for processing, and the whole process lasts for more than 20 minutes; the functions of each slot are respectively, slot 1: washing ultrasound, using the grinding and polishing cleaning agent stock solution of Xinmingyang brand at room temperature, slot 2: washing ultrasound, using the optical glass cleaning agent of Feinel brand, and preparing a 5%-7% cleaning solution with pure water in proportion, the cleaning temperature is 60°C, slot 3: washing ultrasound, using the same cleaning solution as slot 2, the cleaning temperature is 50°C, slot 4: room temperature pure water ultrasound, slot 5: room temperature pure water ultrasound, slot 6: room temperature pure water ultrasound, slot 7: slow air dehydration, slot 8: hot air drying, the drying temperature is 50°C. Further, the whole process lasts for 30-40 minutes.

[0037] Similarly, the cleaning of the sheath in step S3 is used to remove dirt on the surface of the sheath. For example, in step S3, the ultrasonic cleaning is the same as the ultrasonic cleaning of the zinc selenide block.

[0038] In step S3, for example, the pure metal sheath is made of Pd, and the purity is not less than 3N. In one example, in step S3, the wall thickness of the sheath is 0.01-1 mm. Further, the wall thickness of the sheath is 0.05-1 mm.

[0039] In one example, in step S4, the hot melt welding is performed by oxyhydrogen flame welding, thereby achieving the sealing of the sheath.

[0040] In one example, in sub-step S51, the vacuum is pumped to less than 50 Pa. Further, the vacuum is pumped to 10-30 Pa.

[0041] In one example, in sub-step S52, the pre-charge pressure is 35-40 MPa. For example, in sub-step S52, the heating rate is 1-10°C / min. For example, in sub-step S52, the temperature is raised to 850-970°C. For example, in sub-step S52, the pressure in the furnace is maintained at 180-200 MPa. For example, in sub-step S52, the constant temperature treatment time is 5-15 hours.

[0042] In one example, in sub-step S53, the cooling rate is 0.5-4°C / min.

[0043] In one example, in step S6, rough polishing is to use a polishing machine to polish the surface of the zinc selenide block to a surface roughness of no more than Ra0.03 μm, which is used to detect material quality. The rough polishing method is the same as step S1.

[0044] In one example, in step S1, in the low-quality zinc selenide block containing fog layer and fog spots that were screened out, the detection results are as follows: fog layer and fog spots were detected inside the zinc selenide block, there was an absorption peak caused by Zn-H bond near the wavelength of 6.2μm, the average grain size was 34-36μm, and the Knoop hardness was HK 116-117kg / mm 2 In step S6, the test results are: no fog layer or fog spots are detected inside the ZnSe block, the absorption peak caused by the Zn-H bond near the wavelength of 6.2 μm is basically eliminated, the average grain size is 36-41 μm, and the Knoop hardness is HK 114-116 kg / mm 2 .

[0045] [test]

[0046] Example 1

[0047] The method for improving the optical quality of CVD zinc selenide of Example 1 comprises the following steps:

[0048] S1, pretreatment and screening of zinc selenide blocks: the zinc selenide grown by CVD method is cut, ground, roughly polished, and tested to screen out zinc selenide blocks of different quality grades, and then screen out low-quality zinc selenide blocks containing fog layer and fog spots, wherein the grinding is to grind the surface of the zinc selenide block to a surface roughness Ra of 0.08 μm using a grinder, and the abrasive is W16 grade corundum purchased from Dongguan Fuchang Surface Treatment Materials Co., Ltd. The rough polishing is to polish the surface of the zinc selenide block to a surface roughness Ra of 0.03 μm using a polishing machine, and the rough polishing abrasive is W6 grade corundum purchased from Dongguan Fuchang Surface Treatment Materials Co., Ltd. The size of the low-quality zinc selenide block containing fog layer and fog spots is D50mm×10mm (i.e., diameter×thickness), and the zinc selenide block is a round piece. Among the low-quality zinc selenide blocks containing fog layer and fog spots screened out;

[0049] S2, cleaning: ultrasonically clean the low-quality zinc selenide block containing fog layer and fog spots, wherein the ultrasonic cleaning is to use an eight-slot ultrasonic cleaning machine to put the zinc selenide block into the slots in the order of 1-8 for treatment, and the whole process lasts for 30 minutes; the functions of each slot are as follows: slot 1: ultrasonic washing, using the original solution of Xinmingyang brand grinding and polishing cleaning agent at room temperature, slot 2: ultrasonic washing, using the optical glass cleaning agent of Feinel brand, and preparing a 6% cleaning solution with pure water in proportion, and the cleaning temperature is 60°C, slot 3: ultrasonic washing, using the same cleaning solution as slot 2, and the cleaning temperature is 50°C, slot 4: pure water ultrasound at room temperature, slot 5: pure water ultrasound at room temperature, slot 6: pure water ultrasound at room temperature, slot 7: slow air dehydration, slot 8: hot air drying, and the drying temperature is 50°C;

[0050] S3, sheath preparation: pre-make a sheath according to the size of the zinc selenide block, the sheath is made of pure metal material that can withstand the temperature and pressure of hot isostatic pressing, the pure metal sheath is made of Pd with a purity of 4N, and the wall thickness of the sheath is 0.05 mm. The sheath is ultrasonically cleaned, and the ultrasonic cleaning is the same as the ultrasonic cleaning method of the zinc selenide block in step S2;

[0051] S4, package packaging: put the zinc selenide block into a package of suitable size, evacuate the package with a vacuum pump to remove the air in the package, and then seal the package with hot melt welding using hydrogen-oxygen flame welding;

[0052] S5, hot isostatic pressing, comprises the following sub-steps:

[0053] S51, placing the zinc selenide block packaged in step S4 in a standard hot isostatic pressing furnace, vacuumizing the furnace to 10 Pa after closing the furnace, washing the furnace more than 5 times, and exhausting the air in the furnace;

[0054] S52, using argon gas with a purity of 6N as the pressure medium, pre-charged to 40MPa, and then heated to 850℃ at a heating rate of 5℃ / min. The temperature was kept constant at this temperature.

[0055] The gas pressure is 180MPa and the constant temperature treatment time is 5h;

[0056] S53, cooling, cooling to room temperature at a cooling rate of 2°C / min;

[0057] S54, reduce the air pressure to normal pressure;

[0058] S6, taking out the zinc selenide block with the jacket after hot isostatic pressing treatment from the standard hot isostatic pressing furnace, removing the jacket on the zinc selenide block, and rough polishing the zinc selenide block for inspection, wherein the rough polishing is to polish the surface of the zinc selenide block to a surface roughness Ra of 0.03 μm using a polishing machine, and the rough polishing method is the same as step S1;

[0059] in,

[0060] In step S1, among the low-quality zinc selenide blocks containing fog layers and fog spots that were screened out, the detection results were:

[0061] The fog layer and fog spots inside the ZnSe block were detected, such as Figure 3 As shown in the left figure,

[0062] There is an absorption peak caused by the Zn-H bond near the wavelength of 6.2μm, such as Figure 4 As shown, the average grain size is 34 μm, referring to Figure 5 The left picture,

[0063] Nuno hardness is HK 116kg / mm 2 ;

[0064] In step S6, the detection result is:

[0065] No fog layer or fog spots were detected inside the ZnSe block. Figure 3 As shown in the right figure,

[0066] The absorption peak caused by Zn-H bond near 6.2μm wavelength is basically eliminated. Figure 4 As shown, the average grain size is 36μm, referring to Figure 5 The right picture,

[0067] Nuno hardness is HK 114kg / mm 2 .

[0068] Example 2

[0069] The method for improving the optical quality of CVD zinc selenide of Example 2 adopts the following steps:

[0070] S1, pretreatment and screening of zinc selenide blocks: the zinc selenide grown by CVD method is cut, ground, roughly polished, and tested to screen out zinc selenide blocks of different quality grades, and then screen out low-quality zinc selenide blocks containing fog layer and fog spots, wherein the grinding is to grind the surface of the zinc selenide block to a surface roughness Ra of 0.08 μm using a grinder, and the abrasive is W16 grade corundum purchased from Dongguan Fuchang Surface Treatment Materials Co., Ltd. The rough polishing is to polish the surface of the zinc selenide block to a surface roughness Ra of 0.03 μm using a polishing machine, and the rough polishing abrasive is W6 grade corundum purchased from Dongguan Fuchang Surface Treatment Materials Co., Ltd. The size of the low-quality zinc selenide block containing fog layer and fog spots is 50 mm×100 mm×5.04 mm (i.e., width×length×thickness), and the zinc selenide block is a rectangular piece. Among the low-quality zinc selenide blocks containing fog layer and fog spots screened out;

[0071] S2, cleaning: ultrasonically clean the low-quality zinc selenide block containing fog layer and fog spots, wherein the ultrasonic cleaning is to use an eight-slot ultrasonic cleaning machine to put the zinc selenide block into the slots in the order of 1-8 for treatment, and the whole process lasts for 35 minutes; the functions of each slot are as follows: slot 1: ultrasonic washing, using the original solution of Xinmingyang brand grinding and polishing cleaning agent at room temperature, slot 2: ultrasonic washing, using the optical glass cleaning agent of Feinel brand, and preparing a 5% cleaning solution with pure water in proportion, and the cleaning temperature is 60°C, slot 3: ultrasonic washing, using the same cleaning solution as slot 2, and the cleaning temperature is 50°C, slot 4: pure water ultrasound at room temperature, slot 5: pure water ultrasound at room temperature, slot 6: pure water ultrasound at room temperature, slot 7: slow air dehydration, slot 8: hot air drying, and the drying temperature is 50°C;

[0072] S3, sheath preparation: pre-make a sheath according to the size of the zinc selenide block, the sheath is made of pure metal material that can withstand the temperature and pressure of hot isostatic pressing, the pure metal sheath is made of Pd with a purity of 4N, and the wall thickness of the sheath is 1 mm, and the sheath is ultrasonically cleaned, and the ultrasonic cleaning is the same as the ultrasonic cleaning method of the zinc selenide block in step S2;

[0073] S4, package packaging: put the zinc selenide block into a package of suitable size, evacuate the package with a vacuum pump to remove the air in the package, and then seal the package with hot melt welding using hydrogen-oxygen flame welding;

[0074] S5, hot isostatic pressing, comprises the following sub-steps:

[0075] S51, placing the zinc selenide block packaged in step S4 in a standard hot isostatic pressing furnace, vacuumizing the furnace to 20 Pa after closing the furnace, washing the furnace more than 5 times, and exhausting the air in the furnace;

[0076] S52, using argon gas with a purity of 6N as the pressure medium, pre-charged to 37MPa, and then heated to 900℃ at a heating rate of 1℃ / min, and kept at this temperature.

[0077] The gas pressure is 190MPa and the constant temperature treatment time is 10h;

[0078] S53, cooling down to room temperature at a cooling rate of 4°C / min;

[0079] S54, reduce the air pressure to normal pressure;

[0080] S6, taking out the zinc selenide block with the jacket after hot isostatic pressing treatment from the standard hot isostatic pressing furnace, removing the jacket on the zinc selenide block, and rough polishing the zinc selenide block for inspection, wherein the rough polishing is to polish the surface of the zinc selenide block to a surface roughness Ra of 0.03 μm using a polishing machine, and the rough polishing method is the same as step S1;

[0081] in,

[0082] In step S1, among the low-quality zinc selenide blocks containing fog layers and fog spots that were screened out, the detection results were:

[0083] The fog layer and fog spots inside the ZnSe block were detected, such as Figure 6 As shown in the left figure,

[0084] There is an absorption peak caused by the Zn-H bond near the wavelength of 6.2μm, such as Figure 7 As shown, the average grain size is 35 μm, referring to Figure 8 The left picture,

[0085] Nuno hardness is HK 117kg / mm 2 ;

[0086] In step S6, the detection result is:

[0087] No fog layer or fog spots were detected inside the ZnSe block. Figure 6 As shown in the right figure,

[0088] The absorption peak caused by Zn-H bond near 6.2μm wavelength is basically eliminated. Figure 7 As shown, the average grain size is 38 μm, referring to Figure 8 The right picture,

[0089] Nuno hardness is HK 115kg / mm 2 .

[0090] Example 3

[0091] The method for improving the optical quality of CVD zinc selenide of Example 3 adopts the following steps:

[0092] S1, pretreatment and screening of zinc selenide blocks: the zinc selenide grown by CVD method is cut, ground, roughly polished, and tested to screen out zinc selenide blocks of different quality grades, and then screen out low-quality zinc selenide blocks containing fog layer and fog spots, wherein the grinding is to grind the surface of the zinc selenide block to a surface roughness Ra of 0.08 μm using a grinder, and the abrasive is W16 grade corundum purchased from Dongguan Fuchang Surface Treatment Materials Co., Ltd. The rough polishing is to polish the surface of the zinc selenide block to a surface roughness Ra of 0.03 μm using a polishing machine, and the rough polishing abrasive is W6 grade corundum purchased from Dongguan Fuchang Surface Treatment Materials Co., Ltd. The size of the low-quality zinc selenide block containing fog layer and fog spots is D50mm×10.03mm (i.e., diameter×thickness), and the zinc selenide block is a round piece. Among the low-quality zinc selenide blocks containing fog layer and fog spots screened out;

[0093] S2, cleaning: ultrasonically clean the low-quality zinc selenide block containing fog layer and fog spots, wherein the ultrasonic cleaning is to use an eight-slot ultrasonic cleaning machine to put the zinc selenide block into the slots in the order of 1-8 for treatment, and the whole process lasts for 40 minutes; the functions of each slot are as follows: slot 1: ultrasonic washing, using the original solution of Xinmingyang brand grinding and polishing cleaning agent at room temperature, slot 2: ultrasonic washing, using the optical glass cleaning agent of Feinel brand, and preparing a 7% cleaning solution with pure water in proportion, and the cleaning temperature is 60°C, slot 3: ultrasonic washing, using the same cleaning solution as slot 2, and the cleaning temperature is 50°C, slot 4: pure water ultrasound at room temperature, slot 5: pure water ultrasound at room temperature, slot 6: pure water ultrasound at room temperature, slot 7: slow air dehydration, slot 8: hot air drying, and the drying temperature is 50°C;

[0094] S3, sheath preparation: pre-make a sheath according to the size of the zinc selenide block, the sheath is made of pure metal material that can withstand the temperature and pressure of hot isostatic pressing, the pure metal sheath is made of Pd with a purity of 4N, and the wall thickness of the sheath is 0.5 mm. The sheath is ultrasonically cleaned, and the ultrasonic cleaning is the same as the ultrasonic cleaning method of the zinc selenide block in step S2;

[0095] S4, package packaging: put the zinc selenide block into a package of suitable size, evacuate the package with a vacuum pump to remove the air in the package, and then seal the package with hot melt welding using hydrogen-oxygen flame welding;

[0096] S5, hot isostatic pressing, comprises the following sub-steps:

[0097] S51, placing the zinc selenide block packaged in step S4 in a standard hot isostatic pressing furnace, vacuuming the furnace to 30 Pa after closing the furnace, washing the furnace more than 5 times, and exhausting the air in the furnace;

[0098] S52, using argon gas with a purity of 6N as the pressure medium, pre-filling the gas pressure to 35MPa, heating the temperature to 970℃ at a heating rate of 10℃ / min, and maintaining the temperature at this temperature.

[0099] The internal pressure is 200MPa and the constant temperature treatment time is 15h;

[0100] S53, cooling, cooling to room temperature at a cooling rate of 0.5°C / min;

[0101] S54, reduce the air pressure to normal pressure;

[0102] S6, taking out the zinc selenide block with the jacket after hot isostatic pressing treatment from the standard hot isostatic pressing furnace, removing the jacket on the zinc selenide block, and rough polishing the zinc selenide block for inspection, wherein the rough polishing is to polish the surface of the zinc selenide block to a surface roughness Ra of 0.03 μm using a polishing machine, and the rough polishing method is the same as step S1;

[0103] in,

[0104] In step S1, among the low-quality zinc selenide blocks containing fog layers and fog spots that were screened out, the detection results were:

[0105] The fog layer and fog spots inside the ZnSe block were detected, such as Fig. 9 As shown in the left figure,

[0106] There is an absorption peak caused by the Zn-H bond near the wavelength of 6.2μm, such as Fig.10 As shown, the average grain size is 36μm, referring to Fig.11 The left picture,

[0107] Nuno hardness is HK 117kg / mm 2 ;

[0108] In step S6, the detection result is:

[0109] No fog layer or fog spots were detected inside the ZnSe block. Fig. 9 As shown in the right figure,

[0110] The absorption peak caused by Zn-H bond near 6.2μm wavelength is basically eliminated. Fig.10 As shown, the average grain size is 41 μm, referring to Fig.11 The right picture,

[0111] Nuno hardness is HK 116kg / mm 2 .

[0112] The above detailed description is used to describe multiple exemplary embodiments, but this document is not intended to be limited to the explicitly disclosed combinations. Therefore, unless otherwise stated, the various features disclosed herein can be combined together to form multiple additional combinations that are not shown for the sake of simplicity.

Claims

1. A method for improving the optical quality of CVD zinc selenide, characterized in that: Includes steps: S1, pretreatment and screening of zinc selenide blocks: the zinc selenide grown by CVD method is cut, ground, roughly polished, and tested to screen out zinc selenide blocks of different quality grades, and further screen out low-quality zinc selenide blocks containing fog layers and fog spots; S2, cleaning: ultrasonically cleaning the low-quality zinc selenide block containing fog layer and fog spots; S3, package preparation: the package is made in advance according to the size of the zinc selenide block. The package is made of pure metal material that can withstand the temperature and pressure of hot isostatic pressing, with a purity of not less than 3N. The package is ultrasonically cleaned; S4, package packaging: put the zinc selenide block into a package of suitable size, evacuate the package with a vacuum pump to remove the air in the package, and then seal the package with hot melt welding; S5, hot isostatic pressing, comprises the following sub-steps: S51, placing the zinc selenide block packaged in step S4 in a standard hot isostatic pressing furnace, After closing the furnace, vacuum it and clean the furnace more than 5 times to exhaust the air in the furnace; S52, using argon gas with a purity of not less than 5N as the pressure medium, pre-charging the gas pressure to 30-40MPa, heating the temperature to 750-1000°C at a heating rate of 0.5-10°C / min, and performing constant temperature treatment at this temperature, maintaining the gas pressure in the furnace at 100-200MPa, and the constant temperature treatment time is 1-100h; S53, cooling down to room temperature at a cooling rate of 0.1-5°C / min; S54, reduce the air pressure to normal pressure; S6, taking out the zinc selenide block with the jacket after hot isostatic pressing treatment from the standard hot isostatic pressing furnace, removing the jacket on the zinc selenide block, and performing rough polishing inspection on the zinc selenide block.

2. The method for improving the optical quality of CVD zinc selenide according to claim 1, characterized in that: In step S1, The grinding process is to grind the surface of the zinc selenide block by a grinder until the surface roughness is not greater than Ra0.08 μm, and the abrasive is W16 grade corundum purchased from Dongguan Fuchang Surface Treatment Materials Co., Ltd.; The rough polishing is to polish the surface of the zinc selenide block by using a polishing machine to a surface roughness of not more than Ra0.03 μm, and the rough polishing abrasive is W6 grade corundum purchased from Dongguan Fuchang Surface Treatment Materials Co., Ltd.

3. The method for improving the optical quality of CVD zinc selenide according to claim 1, characterized in that: In step S2, ultrasonic cleaning is performed by using an eight-slot ultrasonic cleaning machine to place the zinc selenide block into the slots in the order of 1-8 for treatment, and the whole process lasts for more than 20 minutes; the functions of each slot are respectively, slot 1: washing ultrasonic, using the grinding and polishing cleaning agent stock solution of Xinmingyang brand at room temperature, slot 2: washing ultrasonic, using the optical glass cleaning agent of Feinel brand, and preparing a 5%-7% cleaning solution with pure water in proportion, and the cleaning temperature is 60°C, slot 3: washing ultrasonic, using the same cleaning solution as slot 2, and the cleaning temperature is 50°C, slot 4: pure water ultrasonic at room temperature, slot 5: pure water ultrasonic at room temperature, slot 6: pure water ultrasonic at room temperature, slot 7: slow air dehydration, slot 8: hot air drying, and the drying temperature is 50°C.

4. The method for improving the optical quality of CVD zinc selenide according to claim 1, characterized in that: In step S3, The pure metal sheath is made of Pd, with a purity not less than 3N; The wall thickness of the package is 0.01-1mm; The ultrasonic cleaning is the same as the ultrasonic cleaning method of the zinc selenide block.

5. The method for improving the optical quality of CVD zinc selenide according to claim 1, characterized in that: In step S4, the hot melt welding is performed by oxyhydrogen flame welding.

6. The method for improving the optical quality of CVD zinc selenide according to claim 1, characterized in that: In sub-step S51, the pressure is evacuated to less than 50 Pa.

7. The method for improving the optical quality of CVD zinc selenide according to claim 1, characterized in that: In sub-step S52, Pre-charge pressure to 35-40MPa; The heating rate is 1-10℃ / min; Heating to 850-970℃; Maintain the gas pressure in the furnace at 180-200MPa; The constant temperature treatment time is 5-15h.

8. The method for improving the optical quality of CVD zinc selenide according to claim 1, characterized in that: In sub-step S53, the cooling rate is 0.5-4°C / min.

9. The method for improving the optical quality of CVD zinc selenide according to claim 1, characterized in that: In step S6, rough polishing is to use a polishing machine to polish the surface of the zinc selenide block to a surface roughness of no more than Ra0.03 μm. The rough polishing method is the same as that of step S1.

10. The method for improving the optical quality of CVD zinc selenide according to claim 1, characterized in that: In step S1, among the low-quality zinc selenide blocks containing fog layers and fog spots that were screened out, the detection results were: The fog layer and fog spots were detected inside the ZnSe block. There is an absorption peak caused by the Zn-H bond near the wavelength of 6.2μm. The average grain size is 34-36μm, Nuno hardness is HK 116-117kg / mm 2 ; In step S6, the detection result is: No fog layer or fog spots were detected inside the ZnSe block. The absorption peak caused by the Zn-H bond near the 6.2μm wavelength is basically eliminated. The average grain size is 36-41μm, Nuno hardness is HK 114-116kg / mm 2 .